MODERN TRENDS IN ENSURING GREEN ECONOMY AND SUSTAINABLE DEVELOPMENT (FEATURES AND PROBLEMS OF IMPLEMENTING ECONOMIC REFORMS IN AZERBAIJAN, 2025)
The green economy considers environmental protection as one of its main priorities and in order to achieve this goal involves the implementation of a number of strategies and measures. Environment protection have a fundamental role sustainable development model of the green economy, because economic development is impossible without sustainable use of natural resources and health of ecosystems. This approach not only reduces waste of resource but also ensures the protection of the environment and biodiversity. Recent scientific studies show that although climate change causes significant costs, establishing a green economic system by 2050 is considered the most successful path.Keywords: green economy, green marketing, green economic system, sustainable development, renewable energy